Long‐wave infrared radiation reflected by compression stockings in the treatment of cellulite: a clinical double‐blind, randomized and controlled study. (15th July 2013) - Bagatin, E.; Miot, H. A.; Soares, J. L. M.; Sanudo, A.; Afonso, J. P. J. M.; de, N.; Talarico, S.
Synopsis Background Cellulite refers to changes in skin relief on the thighs and buttocks of women, with a prevalence of 80–90%, causing dissatisfaction and search for treatment. Etiopathogenesis is multifactorial, as follows: herniation of the hypodermis towards the dermis, facilitated by perpendicular fibrous septa, changes in the dermal extracellular matrix, decreased adiponectin, genetic polymorphism, microcirculation alterations and inflammatory process. There are numerous therapeutic approaches, with little evidence of effectiveness. The long‐wave infrared (LWIR) radiation interacts with water, improves microcirculation and stimulates metabolic processes. To date, the use of tissues with potential reflection of LWIR radiation has not been systematically investigated as adjuvant treatment for cellulite. Objective To investigate the efficacy and safety of the treatment of cellulite through the use of compression stockings made with thread reflecting LWIR radiation. Patients and methods Clinical study of therapeutic intervention, controlled and double‐blind, including 30 women, aging from 25 to 40 years, with cellulite of grades II and III on the thighs and buttocks who used compression stockings, "pantyhose" model, made with reflector thread of LWIR radiation, on only one randomized side. Women under other treatments for cellulite and with venous and/or blood insufficiencies were excluded. Evaluation of efficacy by clinical parameters, photographs, Dermatology Life Quality Index (DLQI), cutometry and high frequency ultrasonography and security by observation of adverse events and venous EcoDoppler recordings. Results DLQI scores showed significant reduction; the two‐dimensional high‐frequency ultrasonography showed an insignificant increase in dermal echogenicity as well as other efficacy parameters demonstrated no or slight improvement, with no differences between the sides exposed or not to LWIR; and there were no severe adverse events. Conclusion Compression stockings, with or without thread reflector of LWIR, showed slight effects in the appearance of cellulite, but the treatment determined a positive impact on women quality of life.